The assessment of black soldier fly (Hermetia illucens) pre-pupae, grown on human faecal waste, as a protein source in broiler and layer diets - Van Schoor, Anton Lourens (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2019.